Characteristics of base materials and acrylates used in removable prosthetics in dental practice (review) - Poliukhovych, Yu.I.; Demkovych , A.Ye.; Bondarenko, Yu.I.; Shcherba, V.V.; Lebid, O.I.; Duda, K.M. (Medicni Perspektivi, 2024)
One of the actual problems of modern orthopedic dentistry is the development of optimal materials that, by their physical and chemical properties, would be most biocompatible with the mucous membrane of the oral cavity. The purpose of this work was to substantiate the use of base materials and acrylates for the manufacture of removable prostheses and to increase the effectiveness of orthopedic treatment of patients with complete or partial absence of teeth basing on the review of literary sources. A literature review was conducted using PubMed, Web of Science, SCOPUS, Google Scholar from 2019 to January 2024. There was no restriction on the date of publication or language. Searches were conducted according to MeSH (Medical Subject Headings) using the following search terms: "removable prosthetics", "removable prostheses", "dental base materials", "acrylates", "materials science", "adaptation". A total of 82 sources of literature were selected and processed during the primary analysis. After systematization of the selected information using general scientific methods, 70 most relevant sources remained. Exclusion criteria: publications that did not meet the purpose of this review, publication language other than English and Ukrainian. Used methods: bibliographic and analytical. The relation between the properties of the materials from which the prosthesis is made and the mucous membrane of the prosthetic bed was revealed, and the direct dependence of the quality of the prosthesis, the period of wearing, and the level of oral hygiene was determined. The base material must be easy to use so that the prosthesis can be manufactured and repaired without the use of a significant number of technological processes and equipment. The most common and popular material for manufacturing the bases of partial and complete removable prostheses are acrylates due to their low cost and the simplicity of the application technology, which does not require expensive equipment. The analysis of these literature sources showed that the percentage ratio of the composition of removable prostheses, which includes acrylic plastic, is more than 80%. However, except all existing advantages, they have a number of disadvantages. The main unsatisfactory quality of acrylic prostheses is their negative impact on the tissues of the prosthetic bed, which is reflected in the sensitivity of the mucous membrane and the phenomena of inflammation. Most often, this is manifested as a result of the reproduction of pathogenic microflora, which is concentrated on the surface of the base of the prosthesis. It is worth remembering that removable prostheses are inherently combined irritants that have a whole set of negative effects on the mucous membrane of the prosthetic bed, leading to its chronic inflammation. The above-described negative properties of acrylic plastic became the impetus for the creation of other types of materials. This problem is extremely urgent, and despite the serious resources spent on its elimination, so far no optimal way to increase not only the functionality and durability of the service, but also the safety of using removable orthopedic constructions has been found.